Characterization of socioeconomic status of Japanese patients with atopic dermatitis showing poor medical adherence and reasons for drug discontinuation. Issue 3 (September 2015) - Murota, Hiroyuki; Takeuchi, Satoshi; Sugaya, Makoto; Tanioka, Miki; Onozuka, Daisuke; Hagihara, Akihito; Saeki, Hidehisa; Imafuku, Shinichi; Abe, Masatoshi; Shintani, Yoichi; Kaneko, Sakae; Masuda, Koji; et al.
Highlights: Adherence level in1327 Japanese subjects with atopic dermatitis was assessed with Morisky Medication Adherence Scale-8. Medication adherence level in Japanese subjects with atopic dermatitis was relatively low compared with that of other chronic diseases. The socioeconomic status of patients with poor adherence was characterized. Abstract: Background: Patients' high adherence to medication is indispensable for the management of skin diseases including atopic dermatitis. We previously showed poor medication adherence in Japanese dermatological patients. Objective: This study was conducted to determine the level of adherence to oral or topical medication in Japanese patients with atopic dermatitis, attempting to characterize the socioeconomic status of those patients with poor adherence. Methods: A web questionnaire survey on demographic data as well as adherence level was conducted on patients registered in the monitoring system. Adherence level was assessed with Morisky Medication Adherence Scale-8 (MMAS-8). Among a total of 3096 respondents with dermatological disorders, data of 1327 subjects with atopic dermatitis were extracted and analyzed. Results: More than 80% of subjects felt that both oral and topical medications were safe and efficacious, while less than 60% of them were satisfied with their treatment. Levels of adherence to oral and topical treatments were evaluated with MMAS-8, giving scores of 4.6 and 4.2, respectively. Demographic factors such as gender, marital status, state of employment, alcohol consumption, frequency of hospital visits, and experience of drug effectiveness had a significant impact on the degree of adherence to treatment. Conclusion: Medication adherence level in Japanese subjects with atopic dermatitis was relatively low compared with that of other chronic diseases. Our survey has characterized patients with poor adherence, who are good targets for interventions to maximize potentially limited healthcare resources.